Improvisation and harm avoidance: An ethnographic study of adherence to postnatal care protocols in two hospitals in Southern Ghana. (March 2020) - Yevoo, Linda L.; Agyepong, Irene A.; Gerrits, Trudie; van Dijk, Han
Highlights: The decision to adhere to postnatal care protocols is derived from collective and individual decisions taken by providers. Making use of what is there and reducing harm to oneself and clients influenced midwives' decision-making. A safe and enabling work environment is critical to improving adherence to protocols and quality care provision. Abstract: Providers' adherence to case management protocols can affect quality of care. However, how and why protocols are adhered to by frontline health workers in low- and middle-income countries is not always clear. This study explored midwives' adherence to national postnatal care protocols in two public hospitals in Southern Ghana using an ethnographic study design. Ninety participant observations and 88 conversations were conducted over a 20-months period, and two group interviews held with the midwives in the two hospitals. Data was analysed using a grounded theory approach. Findings: Midwives collectively decided when to adhere, modify or totally ignore postnatal care protocols. Adherence often occurred if required resources (equipment, tools, supplies) were available. Modification occurred when midwives felt that strict adherence could have negative implications for patients and they could be seen as acting 'unprofessionally'. Ignoring or modifying protocols also occurred when midwives were uncertain of the patient's health condition; basic supplies, logistics and infrastructure needed for adherence were unavailable or inappropriate; or midwives felt they might expose themselves or their clients to physical, psychological, emotional, financial or social harm. Regardless of the reasons that midwives felt justified to ignore or modify postnatal care protocols, it appeared in many instances to lead to the provision of care of suboptimal quality. Conclusion and recommendations: Providing clinical decision-making protocols is not enough to improve mother and new born care quality and outcomes. Faced with constraining conditions of work, providers are likely to modify guidelines as part of coping behaviour. Addressing constraining conditions of work must accompany guidelines. This includes adequate risks protection for health workers and clients; and resolution of deficits in essential equipment, infrastructure, supplies and staffing.